Two dimension-reduction probabilistic models for simulating nonstationary turbulent wind fields. (April 2023) - Liu, Zhangjun; Yan, Long; Liu, Yun; Ruan, Xinxin
Abstract: The reasonable modeling of a nonstationary stochastic turbulent wind field is an important basis and premise for the analysis of the wind-induced response and reliability of engineering structures. In the present study, two dimension-reduction probabilistic models are established for simulating the multi-dimensional and multi-variable nonstationary turbulent wind fields based on the double proper orthogonal decomposition (DPOD) and the double spectral representation method (DSRM). Among them, the DPOD, originally used to simulate a stationary turbulent wind field, is extended to a nonstationary one, and the DSRM is a newly proposed method for a nonstationary turbulent wind field with a large number of simulation points. In essence, the DPOD is a discrete method with explicit physical significance and flexible spatial location of simulation points, while the DSRM is a continuous method, of which the simulation efficiency is theoretically independent of the number of simulation points. Furthermore, by introducing the dimension-reduction methods based on random function and POD-FFT (Fast Fourier transform) technique into the DPOD and the DSRM, the nonstationary stochastic turbulent wind field can be effectively described with merely three elementary random variables. Numerical examples of the nonstationary stochastic turbulent wind fields acting on a long-span bridge and a communication tower fully verify the effectiveness and superiority of the proposed methods. Highlights: The DPOD is extended for simulating non-stationary turbulent wind field. The DSRM is proposed for the case with a large number of simulation points. The benefits and drawbacks of the two models are investigated in depth. The proposed models only need 3 basic random variables to realize simulation. The FFT algorithm can be introduced to enhance the simulation efficiency.